Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan PT. Bineatama Kayone Lestari Tasikmalaya - Riska Siti Nurhaliza,; Cece Rakhmat,; Arga Sutrisna, (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine how much influence the leadership style and work environment have on job satisfaction of employees of PT. Binetama Kayone Lestari Tasikmalaya. The research method used is quantitative method with causality method and survey approach. The population in this study amounted to 1372 and the sample taken was 100 respondents. The analytical tool used is multiple linear regression analysis, with hypothesis testing, namely the F test and t test. The results of the study based on the F test showed that the leadership style and work environment simultaneously had a significant effect on job satisfaction. Based on the t test, it shows that the leadership style partially has a significant effect on job satisfaction and the work environment partially has a significant effect on job satisfaction.